Mountain Biodiversity: Reason Behind its High Diversity and its Change with Time - KC, Bhawana (The Initiation, 2010)
Mountain "islands in the sky" covering one fourth of Earth's surface provide goods and services to about half of humanity, with nearly half of all 34 world's biodiversity hotspot concentrated in it. Although retaining inherently greater biodiversity, mountains are facing loss of these natural assets due to various human induced causes of which few to name are deforestation, uphill expansion of agriculture etc. With integrated knowledge of mountain biodiversity change in the pathway of time and threatening factors of mountain biodiversity, we can broaden our horizon of knowledge which can be a milestone in sustainable conservation of biodiversity. This is a review article which endeavors to identify the reasons behind high mountain biodiversity and its increasing vulnerability with time. Key Words: Mountain, Biodiversity, Ecosystem, Temporal change DOI: 10.3126/init.v3i0.2501 The Initiation Vol.3 2009 p.102-113